Synthesis of Glycosides by Glycosynthases - Marc R. Hayes; Jörg Pietruszka (Molecules, 2017)
The many advances in glycoscience have more and more brought to light the crucial role of glycosides and glycoconjugates in biological processes. Their major influence on the functionality and stability of peptides, cell recognition, health and immunity and many other processes throughout biology has increased the demand for simple synthetic methods allowing the defined syntheses of target glycosides. Additional interest in glycoside synthesis has arisen with the prospect of producing sustainable materials from these abundant polymers. Enzymatic synthesis has proven itself to be a promising alternative to the laborious chemical synthesis of glycosides by avoiding the necessity of numerous protecting group strategies. Among the biocatalytic strategies, glycosynthases, genetically engineered glycosidases void of hydrolytic activity, have gained much interest in recent years, enabling not only the selective synthesis of small glycosides and glycoconjugates, but also the production of highly functionalized polysaccharides. This review provides a detailed overview over the glycosylation possibilities of the variety of glycosynthases produced until now, focusing on the transfer of the most common glucosyl-, galactosyl-, xylosyl-, mannosyl-, fucosyl-residues and of whole glycan blocks by the different glycosynthase enzyme variants.